Cattle breeding programs and trait preferences in Ethiopia - Seid, M.E.; Kefenie, K.K.; Gebreyohanes, Gebregziabher; Meseret, Selam; Okeyo Mwai, Ally; Negussie, E. (Science Publications, 2025)
The success of livestock breeding programs depend on the active involvement of smallholder farmers, pastoralists, and agro-pastoralists in shaping breeding objectives and identifying key trait preferences based on specific production goals. This study aimed at assessing the relative importance of cattle-keeping objectives and trait preferences across mixed crop-livestock, pastoral, and agro-pastoral production systems in Ethiopia. We collected data from 180 households 90 from mixed crop livestock, 65from pastoral, and 25 from agro-pastoral systems. The exploded logit statistical model was used and it provided a nuanced understanding of the different cattle-keeping objectives. In mixed crop-livestock systems, draft power and milk production were prioritized, whereas pastoral systems emphasized milk production and calf rearing. Data revealed that agro-pastoral systems demonstrated a more balanced set of preferences, with draft power and milk production being equally important. Trait preferences formal cattle were largely consistent across systems, with traction ability and body size being highly valued, while preferences for other traits, such as coat color and fertility, varied by context. Milk yield was the dominant trait across all production systems. The study outcomes offer crucial insights for the development of balanced breeding programs tailored to the needs of smallholder farmers, pastoralists, and agro-pastoralists, promoting sustainable cattle productivity.